Potassium sulphate induces resistance of rice against the root-knot nematode Meloidogynegraminicola - Mao-yan LIU; De-liang PENG; Wen SU; Chao XIANG; Jin-zhuo JIAN; Jie ZHAO; Huan PENG; Shi-ming LIU; Ling-an KONG; Liang-ying DAI; Wen-kun HUANG; Jing LIU (Journal of Integrative Agriculture, 2022)
Potassium (K), an important nutrient element, can improve the stress resistance/tolerance of crops. The application of K in resisting plant-parasitic nematodes shows that the K treatment can reduce the occurrence of nematode diseases and increase crop yield. However, data on K2SO4 induced rice resistance against the root-knot nematode Meloidogynegraminicola are still lacking. In this work, K2SO4 treatment reduced galls and nematodes in rice plants and delayed the development of nematodes. Rather than affecting the attractiveness of roots to nematodes and the morphological phenotype of giant cells at feeding sites, such an effect is achieved by rapidly priming hydrogen peroxide (H2O2) accumulation and increasing callose deposition. Meanwhile, galls and nematodes in rice roots were more in the potassium channel OsAKT1 and transporter OsHAK5 gene-deficient plants than in wild-type, while the K2SO4-induced resistance showed weaker in the defective plants. In addition, during the process of nematode infection, the expression of jasmonic acid (JA)/ethylene (ET)/brassinolide (BR) signaling pathway-related genes and pathogenesis-related (PR) genes OsPR1a/OsPR1b was up-regulated in rice after K2SO4 treatment. In conclusion, K2SO4 induced rice resistance against M. graminicola. The mechanism of inducing resistance was to prime the basal defense and required the participation of the K+ channel and transporter in rice. These laid a foundation for further study on the mechanism of rice defense against nematodes and the rational use of potassium fertilizer on improving rice resistance against nematodes in the field.